Analisis Kinerja Keuangan UMKM Makanan dan Minuman dalam Naungan Rumah BUMN Rembang (Lembaga Pengembangan Kinerja Dosen, 2026)
The financial performance of MSMEs is the result of a business's success in sustaining itself thru financial management. This research aims to provide information on the impact of financial literacy, payment gateways, and financial inclusion on the financial performance of MSMEs. This investigative activity involves two types of variables: independent variables consisting of financial literacy, payment gateways, and financial inclusion, while the financial performance of MSMEs is the dependent variable. Food and beverage MSMEs under the auspices of Rumah BUMN are the study population, totaling 337. The method for determining the sample size was determined using Slovin's formula, and sampling was conducted using specific criteria, resulting in a sample size of 77 respondents. The data analysis technique involves multiple linear regression analysis. This research activity found that each of the variables used, namely financial literacy, payment gateway, and financial inclusion, has a significant positive impact on the financial performance of MSMEs. The coefficient of determination shows that 91.3% of the variables of financial literacy, payment gateway, and financial inclusion are able to explain the financial performance variable of MSMEs.